Real time dynamic facial recognition of subject at motion using angular image - Tasneem, Sharah; Rahman, Ramisa Yashfi; Mansur, Ayman; Nowshad, MD. Meherab Hossain (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.